Cultural Diversity and Leisure: Experiences of Women in Australia - Taylor, Tracy (Loisir et Société / Society and Leisure)

(untitled) (Presses de l’Université du Québec, 2001)
AbstractThere is a growing body of literature that seeks to better understand the relationships between leisure and cultural diversity. This study explored the leisure experiences of women from culturally diverse backgrounds in the multicultural country of Australia. The research draws comparisons with a similar study in Canada (Tirone and Pedlar, 2000) and comments on the similarities between the two countries in terms of immigration policies and their subsequent impact on the leisure experiences of migrants. It was found that many parallels can be drawn but that there are also apparent differences in the ways which migrants experience leisure. The ultimate conclusion of both studies is the same, leisure participation falls on a continuum and while it can facilitate the valuing diversity, it can also be an alienating experience. Multiethnic countries need to be aware of how attitudes, systems and programs facilitate such outcomes and strive to be more culturally inclusive.